The Design of the Promotional Media as a Form of Anti-Passion Against the Decline of the Economist of Star Mılkshake During the COVID-19 Pandemic - Syaeful Anas Aklani; Aldovanda Haflah Setiawan (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
The use of the internet in human life is made more accessible because the delivery of information and promotion in the MSME sector has become more structured and systematic, which makes visual communication media in the form of video the first choice used in addition to messages in the form of text, brochures or websites. The promotional video is an alternative form to increase the power of visitors and buyers to find MSMEs efficiently and quickly; Star Milkshake is an MSME that is engaged in the culinary field in the form of drinks with various compositions and flavors. In this study, the author uses the MDLC method, which explains in a structured manner starting from conceptualizing, designing, collecting data, collecting data, testing, and distributing. The result of this applied research is the creation of an increase in the economy and income of MSME owners from around 400 thousand per day to 600-750 thousand.